A data-driven structural model of hSSB1 (NABP2/OBFC2B) self-oligomerization - Touma, Christine (Nucleic Acids Res, 2017)
The maintenance of genome stability depends on the ability of the cell to repair DNA efficiently. Single-stranded DNA binding proteins (SSBs) play an important role in DNA processing events such as replication, recombination and repair. While the role of human single-stranded DNA binding protein 1 (hSSB1/NABP2/OBFC2B) in the repair of double-stranded breaks has been well established, we have recently shown that it is also essential for the base excision repair (BER) pathway following oxidative DNA damage. However, unlike in DSB repair, the formation of stable hSSB1 oligomers under oxidizing conditions is an important prerequisite for its proper function in BER. In this study, we have used solution-state NMR in combination with biophysical and functional experiments to obtain a structural model of hSSB1 self-oligomerization. We reveal that hSSB1 forms a tetramer that is structurally similar to the SSB from Escherichia coli and is stabilized by two cysteines (C81 and C99) as well as a subset of charged and hydrophobic residues. Our structural and functional data also show that hSSB1 oligomerization does not preclude its function in DSB repair, where it can interact with Ints3, a component of the SOSS1 complex, further establishing the versatility that hSSB1 displays in maintaining genome integrity.